1999
DOI: 10.1046/j.1365-2435.1999.00287.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of male mating history on paternal investment, fecundity and female remating in the seed beetle Callosobruchus maculatus

Abstract: 1. In many organisms, males provide nutrients to females via ejaculates that can influence female fecundity, longevity and mating behaviour. The effect of male mating history on male ejaculate size, female fecundity, female longevity and female remating behaviour in the seed beetle Callosobruchus maculatus was determined. 2. The quantity of ejaculate passed to females declined dramatically with successive matings. Despite the decline, a male’s ability to fertilize a female fully did not appear to decline subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
127
3
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(142 citation statements)
references
References 48 publications
8
127
3
2
Order By: Relevance
“…Similar reasons for the preference for virgin over non virgins mates have been previously discussed in terms of decline in nutritional gain by females when mated with non virgins rather than virgin males (Jennions & Petrie, 1997;Savalli & Fox, 1999).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Similar reasons for the preference for virgin over non virgins mates have been previously discussed in terms of decline in nutritional gain by females when mated with non virgins rather than virgin males (Jennions & Petrie, 1997;Savalli & Fox, 1999).…”
Section: Discussionsupporting
confidence: 65%
“…Non-random mating is a common phenomenon in insects, with mate choice dependent on a number of factors such as morphology (Majerus et al, 1982a, b;Wang, 2002), age (Hansen & Price, 1995;Kokko & Lindstrom, 1996) and/or mating status (Sakaluk & Ivy, 1999;Savalli & Fox, 1999;Sakaluk et al, 2002). Although sexual activity per se has received less attention in ladybirds, the phenomenon of non-random mating or mate choice has been studied, in polymorphic species, which are convenient experimental models (Hodek & Ceryngier, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Part of this substantial effect of copulation duration on male longevity may be due to the fact that in our population males do not feed or drink as adults, but provide females with a substantial ejaculate that can be up to 10% of body mass (Paukku and Kotiaho, 2005). This means that males are losing both energy and water in their ejaculate, as suggested by the dramatic decline in ejaculate size with successive matings (Savalli and Fox, 1999). It is unclear however, if males that copulate for longer transfer larger ejaculates to females.…”
Section: Male Mating Costsmentioning
confidence: 98%
“…These findings are therefore consistent with a standard assumption of life-history models-investment in reproduction trades-off with longevity (Roff, 2002)-but if and how this trade-off varies across environments (for example, Czesak and Fox, 2003) remains to be investigated. In addition, how further copulations influence this trade-off also needs to be assessed, but male investment is greatest in their first copulation (Savalli and Fox, 1999), which is why we focused on this here. Previous phenotypic findings in this species suggested that mating has a negative effect on male survival (Paukku and Kotiaho, 2005).…”
Section: Male Mating Costsmentioning
confidence: 99%
“…These mating effects are determined mainly by attributes of the male ejaculates, which may vary according to male mating history (Avila et al 2011). Females mating with an already-mated male can incur fitness costs, in terms of reduced egg fertility and fecundity, shorter lifespan, or prolonged duration of copulation (Savalli and Fox 1999;Hughes et al 2000;Lauwers and Dyck 2006;Kant et al 2012). Thus, when able to exercise Communicated by N. Wedell choice, females should prefer to mate with males who maximize their fitness.…”
Section: Introductionmentioning
confidence: 99%